Pengaruh Konten Influencer @EKOZHARAH Di Instagram Terhadap Peningkatan Kemampuan Followers Editing Foto - Andini putri Hapsari, Mochammad Arkansyah (LPPM Stikosa-AWS, 2022)
ABSTRACTThis study aims to determine the level of influence of the content of Influencer @ekozharah on Instagram on increasing the ability of followers in the field of photo editing. The theory used is the theory of S.O.R (Stimulus, Organism, Response). Theory relates between communication messages and reactions. The method used in this study is a quantitative method. By using a questionnaire in drawing conclusions data. The sampling technique in this study used simple random sampling. Based on the research that has been done, the researchers conclude that there is a significant effect of @ekozharah's influencer content on Instagram on increasing the ability of followers in the field of photo editing. The correlation coefficient is 0.631 with a tendency of influence of 65.6%. The communicant is able to receive and process the stimulus from the influencer so that behavior changes occur, namely the communicant's ability to edit photos by 65.6%.Keywords: Influencer, Photo editing, S.O.R . theory